Determination of some elements in the nails in patients with colon cancer using total reflection X-ray fluorescence - Phuong, Huynh Truc; Son, Nguyen An; Ha, Nguyen Thi Nguyet; Sang, Nguyen Thi Minh; Linh, Nguyen Thi Truc; Binh, Dinh Thanh; Loan, Truong Thi Hong; Dung, Ho Manh; Anh, Tran Tuan; Van Dong, Nguyen (Spectrochimica acta. Part B: Atomic spectroscopy, 2021)
Sixty-two subjects (31 men with colon cancer) participated in this study. The analysis of elements in the nails was performed by total reflection X-ray fluorescence (TXRF) technique. The results showed that fifteen elements were quantified, including the following: S, P, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, As, Se, and Br. We have found that there were significant differences in the concentrations of elements Ca, Cr, Fe, Cu, Zn, As, and Se between normal subjects and men with colon cancer (p < 0.05). We conclude that TXRF is a technique suitable for elemental analysis in human nail samples. The concentration of elements Ca, Cr, Fe, Cu, Zn, As, and Se could be among the factors used for the diagnosis of colon cancer risk in men. [Display omitted] •The study was conducted on nail samples collected from 62 men dividing into healthy and colon cancel groups.•Total reflection X-ray fluorescence (TXRF) technique was successfully used for elemental analysis in nail sample.•The elements, P, S, K, Ca, Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, As, Se, and Br, were detected and analysed.•The elements Ca, Cr, Fe, Cu, Zn, As, and Se were found to have good correlation with colon cancer.